2018
DOI: 10.5606/archrheumatol.2017.6127
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-analysis of Prevalence of Biopsy-Proven Lupus Nephritis

Abstract: Objectives: This study aims to conduct a meta-analysis to clarify the epidemiologic characteristics of biopsy-proven lupus nephritis (BPLN), including those relating to its prevalence and prognosis. Patients and methods: A literature search for relevant studies was conducted in the electronic databases of PubMed, Google Scholar, Embase, and Cochrane trial register. The following search terms were used for original articles published between January 1982 and April 2016: "lupus nephritis" or systemic lupus eryth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 33 publications
5
43
0
1
Order By: Relevance
“…These results coincide with the meta-analysis study of Wang et al. 34 that indicated that class IV LN was the most frequent pathological type in all their examined studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results coincide with the meta-analysis study of Wang et al. 34 that indicated that class IV LN was the most frequent pathological type in all their examined studies.…”
Section: Discussionsupporting
confidence: 91%
“…A meta-analysis conducted by Wang et al. 34 also revealed that the majority of patients were middle-aged females. A female preponderance could be explained by the effect of sex hormones, which have immune-modulating and cellular protective effects following tissue damage.…”
Section: Discussionmentioning
confidence: 96%
“…Renal involvement in the chronic autoimmune disease systemic lupus erythematosus (SLE), manifesting as lupus nephritis, is common, with a prevalence of up to 48% of SLE patients ( 67 ), and is usually associated with poor outcome. Pathological features consist of glomerulonephritis and glomerular crescents, infiltration of inflammatory cells in the kidney’s epithelium, podocyte injury, immune complex deposition on mesangial cells, and vascular and tubulointerstitial lesions ( 68 ).…”
Section: Inflammatory Kidney Diseases With Complement Involvementmentioning
confidence: 99%
“…Class III and IV LN (Focal and Diffuse LN) bear the most severe prognosis and require prompt immunosuppressive treatment. A metanalysis evaluating the prevalence of biopsy-proven LN [ 37 ] identified class IV as the most prevalent and the one associated with the highest risk of progression to ESRD. A total of 15–30% of patents with class IV do not reach remission and 15–30% of those reaching remission will develop a relapse.…”
Section: Introductionmentioning
confidence: 99%